Non-Arteritic Anterior Ischaemic Optic Neuropathy – Myths and Misconceptions: Experience from a Tertiary Care Centre in North India. (3rd July 2020) - Patil, Anuja; Mahesh, Kartik Vinay; Prabhat, Nandita; Singh, Ramandeep; Takkar, Aastha; Ray, Sucharita; Tandyala, Naresh; Goyal, Manoj Kumar; Lal, Vivek
ABSTRACT: We prospectively evaluated 22 consecutive patients (24 eyes) suffering from non-arteritic anterior ischaemic optic neuropathy (NAION) at a tertiary care centre in Northern India. The mean age was 51.7 years. Visual loss on awakening was noticed only in three (12.5%) eyes. Six (27.3%) patients had headache while three (9.7%) patients had retro-orbital pain at the onset of visual loss. Peripapillary haemorrhages were seen in two (8.3%) eyes. At follow up, only one eye showed improvement in visual acuity. The results of our study suggest that NAION may not always present with the classic clinical picture. Accordingly, a high index of suspicion remains the key to correct diagnosis.